Workplace enviroment factors influencing transfer of training in Sarawak Energy Berhad - Edwina, Mandak (Universiti Malaysia Sarawak (UNIMAS), 2011)
Training is regarded as an obligatory cost in many of today's progressive organizations. However, the return on hefty investment in training is still questionable with general estimate of less than 20%. The acquisition of knowledge, skills, behaviors, and attitudes during training period contributes little value if these are not transpired to the workplace after completion of program. The understanding of how to support transfer of training is important in order for training programs to really improve organizational and individual performance. The purpose of this research is to examine the influences of workplace environment factors i.e. supervisor support, peer support, opportunity to use, influence of reward system, knowledge sharing culture, openness to change towards the transfer oftrainin~ The data for analysis is from survey questionnaires completed by 100 technical employees that has attended technical training programs conducted by Syarikat SESCO Berhad Training Center. Opportunity to use the learning and supervisor support has been found to be significant factors in predicting effective transfer of training in this research setting. Reward system, peer support, knowledge sharing and openness to change also indicated positive links with transfer of training. Reward system turned out as a weak predictor towards training in this population. Knowledge sharing and openness to change seem to have a more indirect effect towards transfer and further studies is recommended better understand the way organizational culture influences the whole process. The present study has achieved its objectives in examining the influences of workplace environment factors towards transfer of training. The research provides recommendations to HRD practitioners by listing the measures that can be taken to create a working environment that is more supportive to transfer process. The findings also provide evidence that can further enhance the knowledge in the area ofoccupational training.